Analisis Komponen Desain Layout, Warna, dan Kontrol User Interface terhadap User Experience pada Aplikasi PeduliLindungi - Ovila Victoria; Fergie Joanda Kaunang; Elmor Benedict Wagiu (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
One of the reasons for the increasing use of smartphones today is the increasingly diverse mobile applications. With the increasing number of mobile applications circulating, more and more application makers are also competing to create applications that satisfy users both in terms of system and appearance. The user interface is one of the factors that influence the user experience. The user interface is not only concerned with aesthetics but also must create a good user experience. Not only the overall appearance, even small details such as buttons or icons can affect the user experience in using a mobile application. If users are happy with the appearance of the mobile application's user interface, users will certainly use the mobile application more often. In this study, an analysis of the user interface design components in the PeduliLindungi application was carried out on the user experience. The analysis was carried out by distributing questionnaires referring to 10 variables of the Heuristic Evaluation method to respondents, where respondents gave an assessment of the aspects in the application to determine the severity rate. Severity rate is an assessment of the level of damage or deficiency in the application. From the calculation results, it is found that the average severity rate is 1,298, which means that it is on a cosmetic problem scale or just a simple design problem that is not a top priority for making application improvements.